اتجاهات التلاميذ المقبلين على امتحان شهادة البكالوريا نحو محتوى الحصص الإعلامية المقدمة من طرف مستشاري التوجيه و الإرشاد المدرسي و المهني - دوباخ, قويدر; كحول, شفيقة (جامعة الوادي - University of Eloued, 2022)
ملخص : هدفت الدراسة إلى التعرف على اتجاهات التلاميذ المقبلين على امتحان شهادة البكالوريا نحو الحصص الإعلامية المقدمة لهم من طرف مستشاري التوجيه و الإرشاد المدرسي و المهني،و بإتباع خطوات المنهج الوصفي و الاعتماد على المقابلة الغير موجهة كأداة لجمع المعلومة من عينة قوامها100 مبحوث اختيرت بطريقة عنقودية ، حيث توصلت الدراسة إلى وجود فائدة كبيرة و ارتياح كبيرة للحصص الإعلامية المقدمة لهم و هذا ما عكسته تحقيق كل الفرضيات الخمسة المترجمة لمهام مستشاري التوجيه و الإرشاد المدرسي و المهني في الجانب الإعلامي. Abstract : The study aimed to identify the attitudes of students who are going to take the baccalaureate exam towards the media sessions provided to them by the school and vocational guidance counselors, and by following the steps of the descriptive approach and relying on the undirected interview as a tool for collecting information from a sample of 100 respondents selected in a cluster manner.Where the study found a great benefit and great satisfaction with the media quotas provided to them, and this was reflected in the achievement of all the five hypotheses translated for the tasks of school and vocational guidance and counseling counselors in the media side.
دراسة ميدانية بثانوية المجاهد بلونار رأس القرية –بسكرة
مقال
Keywords: اتجاهات ؛ حصص إعلامية ؛ توجيه مدرسي و مهني ؛ مستشار التوجيه والإرشاد المدرسي و المهني; directions ; media classes ; school and vocational guidance ; school and vocational guidance and counseling